PENGARUH PENGGUNAAN MEDIA FLASHCARD TERHADAP KEMAMPUAN BERPIKIR SIMBOLIK ANAK USIA 4-5 TAHUN DI TK NEGERI 54 TALANG BUKIT - Devit Ekayanti; Hendra Sofyan; Asih Nur Ismiatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of using flashcard media on the symbolic thinking ability of children aged 4–5 years at TK Negeri 54 Talang Bukit. The study employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The research subjects consisted of an experimental group (10 children) and a control group (7 children). The experimental group was taught using flashcard media, while the control group used conventional learning media. Data were collected through observation of children’s symbolic thinking abilities and analyzed using descriptive statistics, normality and homogeneity tests, and hypothesis testing with an Independent Sample t-test. The results showed that the mean score of symbolic thinking ability in the experimental group increased from 18 in the pretest to 27.70 in the posttest, while the control group increased from 17 to 20.29. The hypothesis test revealed a Sig. (2-tailed) value of 0.000 with a t-value of 5.568, which was higher than the t-table value of 1.753, indicating a significant difference between the experimental and control groups. These findings indicate that the use of flashcard media has a significant effect on the symbolic thinking ability of children aged 4–5 years. Therefore, flashcard media can be used as an effective learning medium to stimulate early childhood cognitive development, particularly in developing symbolic thinking skills as a foundation for literacy and numeracy development at subsequent educational levels.